1974
DOI: 10.1073/pnas.71.3.662
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Heavy Chain Messenger RNA from Myogenic Cell Cultures

Abstract: The appearance of messenger RNA for myosin heavy chains in chick-embryo myogenic cell cultures was investigated. Total polyribosomes were isolated from cultures at various times of development and were purified in sucrose step gradients. These polysomes were either extracted with phenol or were treated with puromycin. The ribonucleoprotein particles and ribosomal subunits released by puromycin were fractionated on sucrose gradients. RNA from polysomes or from puromycin-dissociated subunits was fractionated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The actin and myosin in 1-day cultures were of the cytoplasmic type occurring in chondroblasts or fibroblasts as well, but in 4-day cultures of fusion-arrested cells typical muscle proteins were present (CHI et al 1975a;HOLTZER et al 1977). PRZYBYLA and STROHMAN (1974) and DEVLIN and EMERSON (1979) did not find messenger RNA coding for any of the contractile proteins before fusion had commenced, indicating that the specific mRNA species begin to coordinately accumulate at fusion. PRZYBYLA and STROHMAN (1974) and DEVLIN and EMERSON (1979) did not find messenger RNA coding for any of the contractile proteins before fusion had commenced, indicating that the specific mRNA species begin to coordinately accumulate at fusion.…”
Section: B) Stages Of Differentiationmentioning
confidence: 91%
“…The actin and myosin in 1-day cultures were of the cytoplasmic type occurring in chondroblasts or fibroblasts as well, but in 4-day cultures of fusion-arrested cells typical muscle proteins were present (CHI et al 1975a;HOLTZER et al 1977). PRZYBYLA and STROHMAN (1974) and DEVLIN and EMERSON (1979) did not find messenger RNA coding for any of the contractile proteins before fusion had commenced, indicating that the specific mRNA species begin to coordinately accumulate at fusion. PRZYBYLA and STROHMAN (1974) and DEVLIN and EMERSON (1979) did not find messenger RNA coding for any of the contractile proteins before fusion had commenced, indicating that the specific mRNA species begin to coordinately accumulate at fusion.…”
Section: B) Stages Of Differentiationmentioning
confidence: 91%
“…The emergence of myoblasts bears on a second contention, namely, that fusion is required to initiate transcription of myosin mRNA, or to activate the translation of inactive myosin mRNA (19)(20)(21)(22)(45)(46)(47)(48). The emergence of mononucleated myoblasts with thick and thin filaments demonstrates that fusion is not a prerequisite event for coordinated expression of the myosin and actin genes.…”
Section: Differential Response Of Replicating and Post-mitotic Cells Tomentioning
confidence: 99%
“…Coleman and Coleman (1968) and Yaffe and Dym (1972) de tected no myosin synthesis in prefusion muscle cultures, and, although Paterson and Strohman (1972) In contrast to these results, however, other workers have tried unsuccessfully to isolate from extracts of mononucleated myogenic cells a mMA that would direct synthesis of myosin heavy chains in a reticulocyte protein-synthesiz ing assay (Pryzbyla et al», 1973; Pryzbyla and Strohman, 1974;Strohman et al, 1974-),…”
Section: ^2mentioning
confidence: 82%
“…Rather than attempting indirect studies, such as those reported by Buckingham et al (197^), and in view of the uncertainties involving ability to quantitatively initiate protein synthesis on myosin mRNA's (Heywood and Nwagwu, 1969) or to assay purified myosin mRNA in a cellfree assay as attempted by Strohman and coworkers (Pryzbyla et al, 1973;Pryzbyla and Strohman, 197^;Strohman et al, 197'+), a more direct approach was taken. If prefusion muscle cells synthesize myosin, then these cells must con tain myosin polysomes.…”
Section: ^2mentioning
confidence: 99%
See 1 more Smart Citation